2019
DOI: 10.1063/1.5092754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of negative ions on discharge characteristics of water plasma source for a miniature microwave discharge ion thruster

Abstract: This work analyzes the discharge characteristics of water plasma for a miniature microwave discharge ion thruster via three-dimensional particle-in-cell simulations with Monte Carlo collisions. It incorporates the negative ions (H À , O À , and OH À ) into the simulation code, aside from the three major positive ion species (H 2 O þ , OH þ , and H þ ), and investigates their effects on the discharge characteristics. On the one hand, the simulation results indicate that H 2 O þ is the dominant species and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In a further investigation of the time evolution of the electron density, we observed characteristic plasma structures in the different magnetic fields, i.e., rotating spokes similar to the phenomena observed in HiPIMS 27 and the striped pattern fluctuations observed in our previous studies. 8,22,23 In MF-1 and MF-3, both rotating spokes and striped pattern fluctuations were seen, while only striped patterns were observed in MF-2; these differences can be explained by the Bohm diffusion coefficient,…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a further investigation of the time evolution of the electron density, we observed characteristic plasma structures in the different magnetic fields, i.e., rotating spokes similar to the phenomena observed in HiPIMS 27 and the striped pattern fluctuations observed in our previous studies. 8,22,23 In MF-1 and MF-3, both rotating spokes and striped pattern fluctuations were seen, while only striped patterns were observed in MF-2; these differences can be explained by the Bohm diffusion coefficient,…”
Section: Discussionmentioning
confidence: 94%
“…The 3D PIC-MCC simulations were based on our previous papers. 8,[22][23][24] In the simulations, we employed the following assumptions: (i) only singly charged xenon ions and electrons are treated as particles;…”
Section: A Calculationmentioning
confidence: 99%
“…A previous study on the water plasma source revealed that the number density of the total negative ions was at least one order of magnitude smaller than that of electrons under the condition shown in Table I. 18 This result indicates that the extracted negative ion currents have little effect on the neutralization performance of the water neutralizer. Hence, we took into account only electrons for the performance evaluation.…”
Section: Additional Remarksmentioning
confidence: 78%
“…based on our previous papers. [15][16][17][18][19] First, we set the initial conditions; then, we solved Maxwell's equations using the FDTD algorithm for the electromagnetic fields of the microwaves to obtain a steady-state solution without plasma. Second, we conducted electrostatic PIC-MCC simulations using the time-varying electric field of microwaves calculated by the FDTD algorithm, the electrostatic electric field of plasma, and the magnetic fields produced by permanent magnets.…”
Section: A Calculationmentioning
confidence: 99%
See 1 more Smart Citation